FREQUENCY OF URINARY STRESS INCONTINENCE DURING PREGNANCY AND POSTPARTUM (The Research of Medical Science Review, 2025)
Background: Several women experience SUI during pregnancy and the postpartum days because of changes related to childbearing. It influences people’s quality of life and regular activities, though often not a lot is said about it. To raise awareness and help with early treatment, this study reviews the rate of SUI in a tertiary care center. Objectives: To determine the frequency of stress urinary incontinence during pregnancy and postpartum period. Study Design: A Descriptive Study Duration And Place of Study: The study will be conducted for 6 months after approval of the synopsis.The study will be conducted in the department of Gynae/ Obstetrics Unit A, Saidu Teaching Hospital, Swat. Methods: A descriptive study was done at Gynae/Obs Unit A in Saidu Teaching Hospital over six months. A total of 363 women, aged 18 to 40, who were pregnant or had given birth in the past 42 days, were included using what is called non-probability consecutive sampling. Data were collected by filling out a form and then checked with SPSS, a program to help with statistics. Chi-square and Fisher’s exact test were used, and a result was considered statistically significant if it had a p-value of 0.05 or below. Results: Participants on average were 28.6 years old ± a range of 4.2 years. Among those who were pregnant, SUI happened in 38.3% of cases, compared to 29.6% of those who had children. Vaginal delivery was more closely linked with SUI than cesarean section (p = 0.032). Women who live in rural areas and belong to the low socioeconomic status group reported a higher rate of incontinence with p-values of 0.041 and 0.048, respectively. The frequency was also higher in women who had more than one pregnancy than in those who were going through their first one (p = 0.038). According to the research, both a woman’s age and experience with childbirth affect her chances of developing SUI. Conclusion: Many women who experience vaginal childbirth, a higher number of children, and low standing of economic ability are prone to stress urinary incontinence both during pregnancy and after. Being screened during antenatal check-ups, having counseling, and doing pelvic floor exercises can lower the chances of having the condition. More research over a longer period will help identify long-term approaches for preventing these diseases. Training must be given to medical staff so they can detect and monitor SUI in postpartum patients.